ANALISIS TERHADAP PELATIHAN DAN PENGEMBANGAN KARYAWAN BAGI PENINGKATAN KINERJA DI PEGADAIAN CABANG X - Fajrina Ajeng Alifah; Sania Murtafia Dara Jati (IJESM Indonesian Journal of Economics and Strategic Management, 2024)
In an era of competitive globalization, companies must further improve the quality of human resources. Effective measures are employee training and further development. The purpose of this study is to understand the implementation of the training and development program of employees at Pegadien and to understand the supporting and inhibiting factors of the program's implementation. This study adoed a qualitative approach with procedures for documentation study data collection, and content analysis. Data is obtained from documents related to policies, materials, evaluations, and annual reports held by Pegadaian. Research results show that Pegadaian has a structured planning, implementation, and evaluation system for its training and development programs. Various training methods are applied, such as on-the-job, off-the-job, and self-development. The evaluation was conducted thoroughly to measure satisfaction, competency changes, and impact on performance. The main supporting factors are management commitment, learning culture, adequate infrastructure, and partnership with training institutions. Impeding factors include limited resources, change resistance, time constraints, impact measurements, and less oimal knowledge transfer.